Characteristics of filtered neutron beam energy spectra at Dalat Reactor - Tran, Tuan Anh (Scientific Research Publishing, 2023)
Filtered neutron technique was applied for producing quasi-monoenergetic neutron beams of 24 keV, 54 keV, 133 keV and 148 keV at the horizontal neutron channel No. 4 of the Dalat Nuclear Research Reactor. The study on physical characteristics of these beam lines has been carried out for efficient applications in neutron capture experiments. The filtered neutron spectrum of each beam has been simulated by Monte-Carlo method and experimentally measured by a gas-filled protonrecoil spectrometer. The neutron fluxes of these filtered beams were measured by the activation technique with standard foils of 197Au, using a high efficient HPGe digital gamma-ray spectrometer.